Multiple plant regeneration from matricular substance released from explants of Citrus jambhiri - MANCHANDA, POOJA; KALIA, ANU; SIDHU, GURUPKAR S; RATTANPAL, H S; KAUR, KULJOT; KAUR, SIMRANJEET (The Indian Journal of Agricultural Sciences, 2020)
Comparative performance of epicotyl-, hypocotyl-, and cotyledonary (Cot) explants for direct organogenesis was evaluated with best response on BAP (3.5 mg/l) + NAA (0.5 mg/l) supplemented MS medium for Cot explants. This differential behaviour can be attributed to diversity and concentration of phytohormone(s), signal phenolics and other compounds. This study identifies the spatio-specific variabilities of these compounds leading to emergence of multiple shoots from explant’s injured regions indicated by formation of foamy-white exudate, ‘matrix’. Topographically, matrix appeared amorphous containing granulation. Further, FT-IR spectra indicated possible presence of woundinduced sugars and phytohormones. Likewise, LC-MS study revealed presence of diverse sugars, phytohormone (PH)/ PH-like and signal compounds. This study illustrates possible interactive roles played by spatial co-localization of these compounds at wounded cut ends of explants for multiple in vitro shoot organogenesis. This study put-forth a novel concept of localized occurrence of multiple primary and secondary metabolites at cut/wounded ends of citrus explants which led to emergence of multiple shoots. These results are promising and could serve the basis for further investigations on various other citrus species for diversity and quantity of various metabolites during in vitro cultivation.